Imaging the hydrogenation of Mg thin films. (31st August 2017) - Hadjixenophontos, Efi; Roussel, Manuel; Sato, Toyoto; Weigel, Andreas; Stender, Patrick; Orimo, Shin-ichi; Schmitz, Guido
Abstract: Among the metal hydride materials, magnesium (Mg) and its alloys show excellent performance for hydrogen storage. The main drawback is the slow hydrogen absorption and desorption kinetics, the sole barrier to commercial adoption. In this work we use Mg thin films as model materials in order to study these kinetics, and observe the growth process of the hydride. Palladium (Pd) is used as a catalyst coating for improving the conditions of hydrogenation. The hydride formation is followed by in-situ X-ray diffraction. Microscopic imaging of the co-existence of Mg and MgH2 is presented. The microstructure change is clearly visible in the micrographs, despite the fact that sample preparation damages the hydride phase. The transformation from columnar grains of the as-deposited Mg thin film, to a grainy equi-axed structure film indicate that the hydride is observed. The hydride is immediately formed at the interface between the Pd and the Mg thin film and grows in a layer-like reaction towards the substrate (SiO2 ). These combined techniques provide an efficient methodology to follow the kinetics of hydride formation within the layer, and study further the diffusion coefficients and mechanism of hydrogenation. Abstract : Growth process of magnesium hydride formation at 5 bars and 150 °C in Mg thin films. Lattice expansion of Mg is observed over hydrogen loading. Nano-cystallization of Mg during hydrogenation. Texture change from columnar grain structure to an equiaxed grainy over H loading. MgH2 grows in a layer-like reaction towards the substrate, visible by TEM images.